Performance indicators evaluation of the population-based breast cancer screening programme in Northern Portugal using the European Guidelines. Issue 5 (October 2015) - Bento, Maria José; Gonçalves, Guilherme; Aguiar, Ana; Castro, Clara; Veloso, Vitor; Rodrigues, Vítor
Highlights Breast cancer screening in Northern Portugal was highly accepted by the population. Most performance indicators met the desirable levels of the European Guidelines. Results were consistent with an effective screening programme. Favourable steps towards a higher coverage of the programme have been taken.